2D or Not 2D: Strain Tuning in Weakly Coupled Heterostructures. (31st January 2018) - Wang, Ruining; Lange, Felix R. L.; Cecchi, Stefano; Hanke, Michael; Wuttig, Matthias; Calarco, Raffaella
Abstract: A route to realize strain engineering in weakly bonded heterostructures is presented. Such heterostructures, consisting of layered materials with a pronounced bond hierarchy of strong and weak bonds within and across their building blocks respectively, are anticipated to grow decoupled from each other. Hence, they are expected to be unsuitable for strain engineering as utilized for conventional materials which are strongly bonded isotropically. Here, it is shown for the first time that superlattices of layered chalcogenides (Sb2 Te3 /GeTe) behave neither as fully decoupled two‐dimensional (2D) materials nor as covalently bonded three‐dimensional (3D) materials. Instead, they form a novel class of 3D solids with an unparalleled atomic arrangement, featuring a distribution of lattice constants, which is tunable. A map to identify further material combinations with similar characteristic is given. It opens the way for the design of a novel class of artificial solids with unexplored properties. Abstract : A strain engineering pathway in weakly bonded heterostructures consisting of layered chalcogenide materials is established. Such heterostructures behave neither as fully decoupled two‐dimensional materials nor as covalently bonded materials. Thus, a novel class of three‐dimensional solids featuring a tunable distribution of lattice constants is formed. A map to identify further material combinations with similar characteristic is given.